Solid-state and solution structural properties of copper(I) compounds with bidentate phosphane ligands - Comba, Peter (European journal of inorganic chemistry, 1999)
The copper(I) compounds [Cu(dppe)2]X [X = BF4−, I−; dppe = 1,2-bis(diphenylphosphanyl)ethane], [Cu(dppp)2]X [X = BF4−,I−; dppp = 1,3-bis(diphenylphosphanyl)propane], [Cu2(dppe)3I2], and [Cu2(dppe)2I2] have been prepared and their structural properties in solution and in the solid state have been determined. 1H-, 13C-, and 31P-NMR spectra in solution [variable temperature and anion (I−) concentrations] and analyses of solids (mass spectra, elemental analyses, and CPMAS 31P-NMR spectra) are interpreted with equilibria in solution that involve two mono- and two dinuclear species. The structures of [Cu(dppe)2]ClO4, [Cu(dppp)2]BF4, and [Cu2(dppe)3I2] · 2 CHCl3 have been analyzed by X-ray crystallography. In all three structures the copper(I) center adopts a distorted tetrahedral geometry.